Lay health advisers: scoping the role and intervention landscape - Carr SM; Lhussier M; Forster N (Dove Medical Press, 2017)
Susan M Carr,1–3 Monique Lhussier,1,3 Natalie Forster1,3 1Public Health Research, Department of Social Work, Education, and Community Wellbeing, Northumbria University, Newcastle upon Tyne, UK; 2Department of Education and Training, Federation University Australia, Ballarat, VIC, Australia; 3Fuse, Centre for Translational Research in Public Health, Newcastle upon Tyne, UK Abstract: The use of lay health advisers has become an established approach within public health, in particular for impact on health inequalities and engaging socially excluded groups. Evidence on how differences in terms of the multiple role dimensions impact the outcomes of programs is limited. This creates ambiguity for decision makers on which roles should be implemented in different contexts for different needs. This paper applies realist logic to an inquiry to explore the mechanisms that may operate in lay-led intervention models and understand how, why, and in what respect these lead to particular outcomes. It draws on a project focusing on health-related lifestyle advisers and further insights gained from a subsequent related project about outreach with traveler communities. Analysis highlights multiple and potentially interacting aspects of lay health-adviser roles that may influence their success, including characteristics of lay health advisers, characteristics of target populations, purpose or intent of interventions, and how advice is given. A model is proposed from which to examine the contexts and mechanisms of lay health advisers that may impact outcomes, and is subsequently applied to two examples of reported lay health-adviser interventions. The combination of skills and characteristics of lay health advisers must be considered when planning which interventions might be appropriate when targeting specific needs or target populations. Focus only on the peer/layperson distinction may overlook other potentially important skills and mechanisms of action integral to lay health-adviser roles. Keywords: realist logic, lay health advisers, inequalities, hard-to-reach populations, service design